Designing the First Rosarium in Serbia to Fulfill Environmental, Societal, and Economical Purposes - Milana Čurčić; Tijana Narandžić; Biljana Božanić Tanjga; Milica Grubač; Magdalena Pušić Devai; Veljko Šarac; Mirjana Ljubojević (Journal of Zoological and Botanical Gardens)
Specialized botanical gardens such as a rose garden, or rosarium, play a significant role due to their multifunctional nature surpassing simple gene bank assembly. Thus, this study conducted a detailed analysis of a rose garden through field and desk research, SWOT analysis, and ecosystem services assessment, aiming to determine the major strengths and opportunities, as well as weaknesses and threats that can promote or constrain the establishment of the first national rosarium in Serbia. After the analysis, the need for complete green area reconstruction arose to achieve both attractiveness and usefulness. Featuring old varieties, wild species, and companies’ own specific rose collections, the proposed garden has the potential to contribute major ecosystem services reflected in environmental, societal, and economic purposes. Owing to the uniqueness of the breeding program and collections created in the past decade, specific thematic parts—open field or greenhouse classroom, ‘roses under the glass bell’, abundant river flow, pollinators’ shelter, taste garden, and scent garden—are envisaged in the future exemplary rosarium that would not be only a classroom but a showroom for interested nurseries, small-scale functional food producers, flower shops, or amateur gardeners that would become aware of new cultivars and expand their marketing and utilization.